Cosmology Design Products Wears To Pura In Bali - I Nyoman Dana (Institut Seni Indonesia Denpasar, 2017)
Bali is one of the areas in Indonesia that still upholds the customs and arts of traditional culture and is admired by the world community. Customary products to the temple are part of the struggle to keep local wisdom. Design cosmology is a transcendental dimension that has a very complex exploration. Life is deep, also full of uncertainty. Ideas, creativity, passion, and ideals, creativity, concepts that overlap, whether intangible or not. The style in the design is a reflection of the behavior and attitude of human life at a certain time, and in line with the dynamics of life, such as social dynamics, cultural development and value. Design can be a reflection of the times in each period. Designer style can be a product trend if he is able to meet the needs and tastes of society. If the design word would be made to satisfy the needs of the community or the person who would carry out a customary and cultural activity for example, then the draft concept should begin from who and when it will be used, it should be considered as a considerate consideration by a designer, so that what they are designed to be acceptable to users of the design.Bali adalah salah satu daerah di Indonesia yang masih menjunjung budaya adat dan budaya kesenian yang masih dikagumi oleh masyarakat dunia. Produk adat tradisional ke pura merupakan bagian dari perjuangan untuk menjaga kearifan lokal. Desain kosmologi adalah dimensi transendental yang memiliki eksplorasi yang sangat kompleks. Gaya dalam desain merupakan cerminan dari perilaku dan sikap budaya manusia pada waktu tertentu, sejalan dengan dinamika kehidupan, seperti dinamika sosial, perkembangan budaya dan nilai. Desain bisa menjadi cerminan zaman di setiap periode. Gaya perancang bisa menjadi tren jika ia mampu memenuhi kebutuhan dan selera konsumen. Anadai mengatakan, desain akan dibuat untuk memenuhi kebutuhan masyarakat atau orang yang akan melakukan kegiatan adat dan budaya, maka draf konsep harus dimulai dari siapa dan kapan akan digunakan disain, hal ini perlu dilakukan. Disajikan sebagai pertimbangan yang cukup matang oleh seorang desainer, Sehingga apa yang disain mereka dapat diterima oleh pengguna desain.